2017
DOI: 10.1101/194084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of genetic structure of the Sub-Saharan parasitic waspCotesia sesamiae

Abstract: 6Parasitoid life style represents one of the most diversified life history strategies on earth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…All field samples from this lineage ( N = 46 in Branca et al., and N = 35 in Kaiser et al., ) were strictly associated with larvae of the host Sesamia nonagrioides (Noctuidae), feeding mainly on the host plant Typha domingensis (Poales, Typhaceae). The remaining four populations of C. sesamiae identified across Africa show variation in geographic distribution, climate preference, symbiotic bacteria or host range (Branca et al., ). However, the main explanatory factor for the genetic structure of C. sesamiae is association with host species (Branca et al., ), revealing the strong selective pressures imposed by the hosts on the wasp populations.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…All field samples from this lineage ( N = 46 in Branca et al., and N = 35 in Kaiser et al., ) were strictly associated with larvae of the host Sesamia nonagrioides (Noctuidae), feeding mainly on the host plant Typha domingensis (Poales, Typhaceae). The remaining four populations of C. sesamiae identified across Africa show variation in geographic distribution, climate preference, symbiotic bacteria or host range (Branca et al., ). However, the main explanatory factor for the genetic structure of C. sesamiae is association with host species (Branca et al., ), revealing the strong selective pressures imposed by the hosts on the wasp populations.…”
Section: Introductionmentioning
confidence: 95%
“…In other Cotesia species, males are able to locate females searching for hosts, because they are attracted by female sex pheromone and host frass on plant material (Xu et al., ). Microsatellite genotyping of over 600 wasps revealed that C. sesamiae exhibits a genetic structure comprising five major populations (Branca et al., ), which vary in their host range (Branca et al., ) and in parasitic success on different hosts (Gitau, Gundersen‐Rindal, Pedroni, Mbugi, & Dupas, ; Mochiah, Ngi‐Song, Overholt, & Botchey, ). These five C. sesamiae populations include one population recently described as a new species, C. typhae (Kaiser et al., ; Kaiser, Dupas, et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations